2020
DOI: 10.1111/cod.13706
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant positive patch test reactions in FreeStyle‐allergic patients sensitized to isobornyl acrylate

Abstract: Background Concomitant positive patch test reactions in patients sensitized to isobornyl acrylate (IBOA) have rarely been documented. Objectives To report concomitant sensitizations in patients with allergic contact dermatitis (ACD) from the glucose sensor FreeStyle Libre and sensitized to IBOA. Methods In 2019, 26 patients with suspected ACD from FreeStyle Libre were patch tested to a baseline series and to a (meth) acrylate series containing IBOA and 2‐phenoxyethyl acrylate (PEA) 0.1% pet. Diabetes devices a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
35
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 27 publications
6
35
1
1
Order By: Relevance
“…In published case series of ACD from glucose sensors, IBOA was the most common allergen involved. Interestingly, in our series, the frequency of sensitisation to IBOA (30.8%), was similar to previously reported rates by other Spanish authors (35.7%), 15 however, much lower than the frequency detected by authors in other European countries, such as Belgium (69.2% currently and ~80% in the past), 16 Portugal (80.0%), 17 and Finland (80.9%) 18 …”
Section: Discussionsupporting
confidence: 91%
“…In published case series of ACD from glucose sensors, IBOA was the most common allergen involved. Interestingly, in our series, the frequency of sensitisation to IBOA (30.8%), was similar to previously reported rates by other Spanish authors (35.7%), 15 however, much lower than the frequency detected by authors in other European countries, such as Belgium (69.2% currently and ~80% in the past), 16 Portugal (80.0%), 17 and Finland (80.9%) 18 …”
Section: Discussionsupporting
confidence: 91%
“…They had as a mean nine contact allergies. Multiple allergies have been discussed previously with regard to patients using the medical device Freestyle Libre, 11 but that using a medical device, ie a glucose sensor or insulin pump, should be a risk factor for polysensitization can, of course, not be argued from case reports. The patients had been patch tested in an targetted manner with substances that also might be found in the same products.…”
Section: Discussionmentioning
confidence: 99%
“…7 The FreeStyle sensor also contains other potential contact allergens but, as recently demonstrated, no PEA. 3 For the observed coreactivity to the PEA-containing patch test preparation and to the other acrylates, possible explanations include: (a) concomitant sensitization from other sources: given that the boy had already been hospitalized several times, he was potentially at increased risk for cutaneous sensitization to (meth)acrylates from various medical devices and adhesives, including the blood pressure cuff that had been repeatedly applied during previous hospitalizations; (b) crossreactivity between IBOA and PEA, and other acrylates, although IBOA has rarely shown any clear cross-reactivity to other acrylates so far; 3,8 and (c) the positive patch test reaction to PEA may actually have been provoked by IBOA, as recent analyses showed that raw materials of PEA obtained from the industry, as in the present case, may contain acrylate contaminants, which include IBOA. Unfortunately, the particular PEA patch test preparation could no longer be analyzed and we were not able to re-test another preparation containing PEA in our patient.…”
Section: Discussionmentioning
confidence: 99%
“…Readings on day (D)2 and D4 showed positive reactions to many meth(acrylates)(Figure S2 nor to fragrances. 2,3 The blood pressure cuff was sent to the Antwerp laboratory for chemical analysis, based on a previous protocol. 4 These analyses showed the presence of IBOA (10-20 ppm) in the part of the device where the tube is glued to the cuff, the cuff itself, and the velcro adhesive.…”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation